50 YEARS OLDMAN WITH HAEMORRHAGIC STROKE - Putra, Al Husni Hadi Pasca (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Stroke is a clinical syndrome that is characterized by acute focal loss of the brain function, lasting more than 24 hours or causing early death, which is caused either by spontaneous bleeding into the brain tissue, covering brain tissues (Intraserbral spontaneous bleeding or subarachnoid bleeding-hemorrhagic stroke) or inadequate blood supply to the brain as a result of low blood flow, thrombosis, and embolism associated with a vascular, heart or blood disease (ischemic stroke or cerebral infarction). 59 years old man came with a complaint of sloping mouth to the left, weakness at the right arm and right leg, vertigo and nausea-vomiting. Patients admitted had history of hypertension since 1 years ago. Patients also admitted had stroke symptoms since 1 year ago. [J. Agromed Unila 2014; 1(3):257-262] Keywords: hemorrhagic stroke, hypertension, stroke